Meningkatkan Hasil Belajar Siswa Dalam Materi Simbol Sila Pancasila Pada Mata Pelajaran Pendidikan Pancasila Dan Kewarganegaraan (PPKN) Dengan Menggunakan Media Puzzle Pada Siswa Kelas III Di SDN Cilaja 2 Pandeglang - Siti Sofia Nurwahyuni; Rifki Arif Nugraha; Ratna Dewi; Ajeng Mulia Sari (Desanta Publisher, 2023)
Based on initial observations in class III SDN Cilaja 2 Pandeglang, it was found that student problemswere in the way of teaching the teacher who tended to be monotonous and rarely used learning media.Besides that, sometimes the teacher only gave assignments in the form of orders so that students copied thematerial in the textbooks, while some of the students had not master reading and writing skills. This causeslow learning outcomes for students, especially in Civics subjects which are still below the KKM. Toovercome this, it is necessary to apply learning innovations using learning media, one of which is usingPuzzel media with the formulation of the problem